2020
DOI: 10.3390/jcm9103062
|View full text |Cite
|
Sign up to set email alerts
|

Alcohol Septal Ablation versus Septal Myectomy Treatment of Obstructive Hypertrophic Cardiomyopathy: A Systematic Review and Meta-Analysis

Abstract: Surgical myectomy (SM) and alcohol septal ablation (ASA) are two invasive therapies for symptomatic patients with hypertrophic obstructive cardiomyopathy (HOCM), despite medical therapy. This meta-analysis aims to compare the efficacy of the two procedures. We searched all electronic databases until February 2020 for clinical trials and cohorts comparing clinical outcomes of ASA and SM treatment of patients with HOCM. The primary endpoint was all-cause mortality, cardiovascular (CV) mortality, sudden cardiac d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
26
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(28 citation statements)
references
References 44 publications
1
26
0
1
Order By: Relevance
“…However, compared with SM, septal ablation has been associated with a lower decrease in the LVOT gradient, less improvement in symptoms, higher pacemaker implantation and a higher frequency of reinvention. [ 25 , 37 , 49 ]…”
Section: Long-term Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, compared with SM, septal ablation has been associated with a lower decrease in the LVOT gradient, less improvement in symptoms, higher pacemaker implantation and a higher frequency of reinvention. [ 25 , 37 , 49 ]…”
Section: Long-term Resultsmentioning
confidence: 99%
“…As main findings, Bytyçi et al observed a higher rate of pacemaker implantation, higher rates of reintervention and less improvement of clinical symptoms in ASA compared with SM, but in exchange, ASA patients presented lower periprocedural complications [ 25 ].…”
Section: Septal Reduction Therapymentioning
confidence: 99%
“…Dynamic LV obstruction is associated with an unfavorable clinical course and the risk of sudden death and should be considered a therapeutic target in HCM patients [ 18 , 19 , 20 , 21 ]. In symptomatic patients who are unresponsive to medical therapy, septal reduction, including SM or ASA, may be clinically beneficial [ 1 , 2 , 3 , 4 , 5 , 6 , 7 , 22 , 23 , 24 ]. To optimize the septal reduction treatment of obstructive HCM, a careful work-up should address the obstruction mechanisms, exclude the primary causes of mitral regurgitation, and provide an accurate measurement of the thickness of the septum in the TSZ responsible for LV obstruction [ 25 , 26 , 27 ].…”
Section: Discussionmentioning
confidence: 99%
“…This finding is important when selecting HCM patients undergoing ASA with an expected favorable long-term clinical course. Several meta-analyses report a comparable outcome between SM and ASA [ 3 , 6 , 7 , 47 ]. However, the majority of the studies focus ASA results in high-risk elderly HCM population that may be affected by comorbidities, limiting the clinically beneficial impact of the procedure and long-term arrhythmic burden assessment.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation